Phase II study of radiotherapy and temsirolimus versus radiochemotherapy with temozolomide in patients with newly diagnosed glioblastoma without MGMT promoter hypermethylation (EORTC 26082) - Wick, Wolfgang; Platten, Michael; Wick, Antje (Clinical cancer research, 2016)
Purpose: EORTC 26082 assessed the activity of temsirolimus in patients with newly diagnosed glioblastoma harboring an unmethylated O6 methylguanine-DNA-methyltransferase (MGMT) promoter. - Experimental Design: Patients (n = 257) fulfilling eligibility criteria underwent central MGMT testing. Patients with MGMT unmethylated glioblastoma (n = 111) were randomized 1:1 between standard chemo-radiotherapy with temozolomide or radiotherapy plus weekly temsirolimus (25 mg). Primary endpoint was overall survival at 12 months (OS12). A positive signal was considered >38 patients alive at 12 months in the per protocol population. A noncomparative reference arm of 54 patients evaluated the assumptions on OS12 in a standard-treated cohort of patients. Prespecified post hoc analyses of markers reflecting target activation were performed. - Results: Both therapies were administered per protocol with a median of 13 cycles of maintenance temsirolimus. Median age was 55 and 58 years in the temsirolimus and standard arms, the WHO performance status 0 or 1 for most patients (95.5%). In the per protocol population, 38 of 54 patients treated with temsirolimus reached OS12. The actuarial 1-year survival was 72.2% [95% confidence interval (CI), 58.2-82.2] in the temozolomide arm and 69.6% (95% CI, 55.8-79.9) in the temsirolimus arm [hazard ratio (HR) 1.16; 95% CI, 0.77-1.76; P = 0.47]. In multivariable prognostic analyses of clinical and molecular factors, phosphorylation of mTORSer2448 in tumor tissue (HR 0.13; 95% CI, 0.04-0.47; P = 0.002), detected in 37.6%, was associated with benefit from temsirolimus. - Conclusions: Temsirolimus was not superior to temozolomide in patients with an unmethylated MGMT promoter. Phosphorylation of mTORSer2448 in the pretreatment tumor tissue may define a subgroup benefitting from mTOR inhibition. Clin Cancer Res; 22(19); 4797-806. ©2016 AACR.
Gesehen am 27.07.2020